THE ANALYSIS OF THE COSTS AND THE CORRELATION BETWEEN TARIFF AND COST IN THE SECTOR OF CLEAN WATER AND SEWERAGE IN ROMANIA - FÜLÖP ÁRPÁD-ZOLTÁN; BAKÓ KINGA-ERZSÉBET; AVRAM BOITOȘ CAMELIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2017)
The analysis of the costs and of the structure of tariffs for operators in the sector of water and sewage system in Romania are a real challenge. Through this analysis we can form an overview of the costs which may involve in the service of providing clean water and the sewage and wastewater treatment. The costs is analysed both in the cost structure at the enterprise level and in comparison with the income made from the activity (supply of drinking water or treatment of wastewater). In the article we study the cost structure at the level of sector of activity and the correlation between the tariff applied to water and sewer services and size of enterprise, number of employees, wage costs, maintenance and repair costs, energy cost and other variables. The correlations results helps us to make the first steps for the realization of an equation of the cost at the level of the sector of water and sewage system. Another correlation study will be between the applied tariff and the size of the investments made with european co-financing in the framework of the SOP Environment. Through this correlation we determine if the size of the tariffs applied in this sector correlate to the size of the investments made in the SOP Environment.